Elites and democratic development in Russia - Steen, Anton, 1949-; Gelʹman, Vladimir, 1965- (Routledge studies of societies in transition ;, 2003)
The transformation from Communist rule towards democratic development in Russia cannot be fully understood without taking the elites into full consideration. Elites and Democratic Development in Russia examines how elites support and challenge democracy and why they are crucial to Russian democracy in particular. In this innovative volume, twelve respected scholars investigate how elites have affected the transition from Communist rule towards democratic development in Russia. They discuss how the elites' degree of integration on national and regional levels may constitute the main.